People's Experiences and Expectations Regarding the Level of Satisfaction with Health Services in the Digital Era - Wasiyem, Wasiyem; Agustien, Icha; Shandy, Annisa Dwi; Maharani, Febby; Warina, Yunita; Simbolon, Maya; Khairani, Alda; Jeane, Adinda Salsabila Safira (Universitas Ibn Khaldun Bogor, 2025)
ABSTRACT Health services in the current digital era require innovation because they are more effective and efficient in administering hospital services. Health workers tend to not use technology optimally, so this can affect excellent service. The aim of this research is to describe people's experiences and expectations regarding the level of satisfaction with health services in the digital era. This research design method uses a qualitative design, data collection is carried out using participant observation techniques via the Google form web to the wider community. The research results showed that 96 participants identified facilities that were easily accessible to them, how they accessed health services, whether they used digital health services, what obstacles they had in using digital health services, and what their expectations were from BPJS health services and health applications. In the future, the results of this research will become a reference for telemedicine companies or developers to improve the quality of health services and strengthen the health system as a whole. Conclusion: Digital health is utilized by participants or patients in receiving health services and recipients of information through virtual communication, which is effective, efficient and clear service from health workers.